Phytochemicals and Antioxidant Activity of Microalgae Dunaliella salina and Botryococcus braunii - Ali Ridlo; Delianis Pringgenies; Ribka Anindita Br Perangin-angin; Dafit Ariyanto (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research The methanolic extracts of  salinaand B. braunii contained alkaloids, steroids, triterpenoids, flavonoids, and saponins. Chlorophyll a, chlorophyll b, and carotenoids were most abundant in the ethyl acetate extracts of salinaand B. braunii. The maximum total phenolic content was observed in the n-hexane extract of  salina(61.28 mg GAE/g sample) and the ethyl acetate extract of B. braunii (46.94 mg GAE/g sample). The n-hexane extracts exhibited the highest antioxidant activity, whereas saponins were most abundant in the methanol extracts. Abstract Microalgal species such as Dunaliella salina and Botryococcus braunii are reportedly rich in natural antioxidants and phytochemicals. This study aimed to determine the phytochemicals and the antioxidant activity of D. salina and B. braunii. Microalgal samples were obtained from the Brackish Water Cultivation Fisheries Center (BPBAP), Situbondo, East Java. The extracts were prepared using the multilevel maceration method. The antioxidant activity of the algal species was analyzed using 1,1-diphenyl-2-picrylhydraxyl (DPPH). Quantitative analysis revealed that D. salina and B. braunii contained antioxidants, indicated by the appearance of yellow spots on the purple background of the TLC plate. The n-hexane extract of D. salina exhibited the highest antioxidant activity with a half-maximal inhibitory concentration (IC50) of 443.28 ppm, 61.28 mg GAE/g sample of total phenolics, 0.106 mg/g of chlorophyll a, 0.165 mg/g of chlorophyll b, and 1,697 mol/g of carotenoids. In contrast, the ethyl acetate extract of B. braunii exhibited the highest antioxidant activity with an IC50 of 634.55 ppm, 46.94 mg GAE/g sample of total phenolics, 18.146 mg/g of chlorophyll a, 12.592 mg/g of chlorophyll b, and 4573 mol/g of carotenoids. The microalgal species used in this study exhibited extremely weak antioxidant activity.